Multimedia Resource for Self Access: How Students Benefit from It? - Zuraina, Ali (2011)

(untitled)
Tell Me More (TMM) is a multimedia resource from Auralog. It is offered in many languages for instance English, German, Dutch, French and etc. It is used to cater the learning needs of young and adult learners. In Universiti Malaysia Pahang (UMP), TMM is used for self access activity in which it contributes 10% of the overall course works in all the English courses offer in the university. Having used the resource for several years, the current study therefore is conducted to know the learning gain of 76 undergraduates in using the multimedia resource. Content analysis from the entries in one of the English subject’s blog is used as the method in collecting the data for the study. The results from the study indicate that TMM is able to improve pronunciation, ‘test’ sense of patience, assist in presentation skills, teach independent learning, motivate by learning through mistakes and make learning more fun. The pedagogical implication from the study reveals that teacher’s presence is still indispensable although students can ‘self access’ their learning by using the multimedia resource. It is as such since both entities possess unique characteristics and have different roles altogether.